3 - From Epidemic to Pandemic: Covid-19, Insecurity and Development in the Sahel - Tope Shola Akinyetun (Africa Development, 2023)
Security is a sine qua non for development. The Sahel is a troubled region and is described as the hotbed of insecurity in Africa. This state of insecurity was compounded by the outbreak of Covid-19. This article examines the regional impact of the pandemic on insecurity and development. It uses a meta-analysis and reviews secondary data to underscore the security and development imbroglio in the Sahel within the context of Covid-19. It was found that Covid-19 exacerbated the insecurity threat in the region due to pre-existing weak governance, poor capacity, grievances and climate change, which had already resulted in fragility, food insecurity, displacement, loss of livelihood, poverty, unemployment, hunger and a humanitarian crisis. The study concludes that armed groups took advantage of the health crisis to prolong conflicts which, coupled with the pre-existing economic conditions, became anathema to development. The article recommends that governments in the region should increase their health budget and enhance their capacity to respond to health emergencies such as the Covid-19 outbreak. The article further recommends that governments in the Sahelian states should prioritise good governance, improved security and regional cooperation to combat poverty.